RESEPSI PENONTON DALAM FILM UANG PANAI’ - Abd Rahman (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
This study focuses on the audience analysis of the panai money tradition 'in the Uang Panai' film. This film is a local film from Makassar in 2016. This study uses a reception analysis method for the audience and uses a qualitative approach. The data source in this study is a data source consisting of two types of data sources, namely primary data and secondary data. Primary data were obtained from in-depth interviews and FGD (Focus Group discussion), while secondary data were obtained from various literature related to this research. This study makes the film the object of analysis and the audience as the subject of analysis. The findings of this study found the diversity of meanings of the audience about the tradition of panai money "after watching the film Uang Panai which was motivated by the socio-cultural experience, economic status, and gender of the film Uang Panai audience ".